Designing and implementing pharmacogenomics study - Son, Yesim Aydin; Tüzmen, Şükrü; Hizel, Candan Perry (Springer India, 2013)
Pharmacogenomics of today has its origins in the 1950s with pioneering studies of monogenic variations in drug metabolism and pharmacokinetics. With the completion of the Human Genome Project in 2003 and the advances in genomics such as the high-throughput genomics technologies, we are now in the postgenomicsera. This transition is increasingly marked with study of polygenic and multifactorial traits such as common complex human diseases as well as pharmacodynamic differences among populations. Changes that emerge from postgenomics medicine are not, however, limited to seismic shifts in scale and scope of pharmacogenetics research. Importantly, many low-and middle-income countries (LMICs) of the South, Asia-Pacific, Eastern Mediterranean, and the Middle East are becoming notable contributors with rapid globalization of science and increasing access to genomics technologies. This brings about, in parallel, an acute demand for regional capacity building in LMICs so that the future evaluation and implementation of postgenomics technologies in personalized medicine take place in an integrated, sustainable, and equitable manner. This chapter aims to highlight the potential applications and opportunities as well as technical and strategic issues that this field offers to influence medical care. © Springer India 2013.